2006
DOI: 10.1007/s00125-006-0529-4
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine derivative inhibits procoagulant activity of human islet cells

Abstract: Aims/hypothesis The early loss of beta cells after islet cell transplantation has been attributed in part to blood coagulation at the implant site. Tissue factor expressed by beta cells and contaminating duct cells is considered to activate this process. Here, we investigated the ability of N-acetyl-L-cysteine to suppress the in vitro procoagulant activity of duct cells and human islet cell preparations. Materials and methods The effects of Nacystelyn, a salt derivative of N-acetyl-L-cysteine, were first asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…3,[16][17][18] However, it is difficult to apply these anticoagulants in the clinical environment because systemic administration is associated with an increased risk of severe bleeding. 19 Therefore, there is an urgent need to explore new therapeutic target for treating IBMIR with fewer bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…3,[16][17][18] However, it is difficult to apply these anticoagulants in the clinical environment because systemic administration is associated with an increased risk of severe bleeding. 19 Therefore, there is an urgent need to explore new therapeutic target for treating IBMIR with fewer bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated in this study that several concentrations of NAC, lower in concentration than that used in paracetamol intoxications, were not toxic for cultured hepatic cells. Recent works also demonstrated that NAC corrects the TF‐PCA on TF‐expressing pancreatic islets and duct cells 11. NAC is also proposed to ameliorate the early function of the hepatic graft, being able to limit the rate of acute rejection 31.…”
Section: Discussionmentioning
confidence: 99%
“…Following in vitro demonstration of TF‐dependent PCA, we further explored coagulation parameters of a 9‐month‐old Crigler‐Najjar patient before and after cell infusions. Since we recently observed that N‐acetyl‐L‐cysteine (NAC) derivative inhibits TF‐dependent PCA of islet preparations,11 we also investigated the potential of NAC to inhibit in vitro PCA associated with hepatocyte suspensions.…”
mentioning
confidence: 99%
“…Consistent with this approach, a monoclonal anti-TF antibody (CNTO859) has been shown to enhance engraftment in a non-human primate marginal mass model (Berman et al, 2007). In addition to direct inhibition of TF, inhibition of the coagulation system at various stages of activation, for example by using the thrombin inhibitor Melagatran (Ozmen et al, 2002), active siteinactivated FVII (iFVIIa) (Moberg et al, 2002a), N-acetylcysteine (Beuneu et al, 2007), activated protein C (APC) (Contreras et al, 2004), anti-GP IIb/IIIa in combination with APC (Akima et al, 2009) or thrombomodulin (Cui et al, 2009), is able inhibit thromboinflammation in vitro or in vivo. As already mentioned, the complement inhibitor compstatin inhibits the release of C-peptide from pancreatic cells exposed to human plasma .…”
Section: Systemic Administrationmentioning
confidence: 94%